The Influence of Background Motivation on The Mathematics Learning Achievement of Class V Students of SD Negeri 040529 Ajibuhara Tiga Panah District Karo Regency Academic Year 2021/2022 - Regina Sipayung (Journal on Education, 2023)
The purpose of this study was to find out whether learning motivation had an effect on the mathematics learning achievement of fifth grade students at SD Negeri 040529 Ajibuhara, Tiga Panah District, Karo Regency, in the 2021/2022 academic year. This research is a quantitative research with correlation method. The population in this study were all students of SD Negeri 040529 Ajibuhara, Ajibuhara District, Karo Regency for the 2021/2022 Academic Year, a total of 408 students. The sample in this study were students in class VA and VB SD Negeri 040529 Ajibuhara with a total of 69 students. The sampling technique was carried out by means of quota sampling. Data collection techniques in this study were observation, unstructured interviews, questionnaires, and documentation which were analyzed using descriptive statistical analysis. Analysis prerequisite test includes data normality test and regression linearity test. Hypothesis testing includes Product Moment correlation test, and the coefficient of determination. The results showed that: (1) The results of the correlation test showed that there was a correlation coefficient of 0.563 with a significance of 0.001 meaning rcount (0.563) > rtable (0.355). This means that there is a positive correlation between learning motivation and learning achievement of students. (2) The results of the tcount > ttable test are 3.668 > 2.045, so that Ha is accepted. This shows that there is a positive and significant influence of the influence of learning motivation on student achievement. The conclusion from this study is that there is a positive and significant influence between learning motivation and learning achievement of fifth grade students at SD Negeri 040529 Ajibuhara, Tiga Panah District, Karo Regency, 2021/2022 Academic Year. Suggestions for teachers, especially fifth grade elementary school mathematics teachers, to motivate children to be more active in learning mathematics and to find ways that are varied and easier for students to digest.